Gradient electrodeposition of Ni-Cu-W(alumina) nanocomposite coating. (5th October 2016) - Allahyarzadeh, M.H.; Aliofkhazraei, M.; Rouhaghdam, A.R. Sabour; Torabinejad, V.
Abstract: Ni-Cu-W-alumina nanocomposite coatings with functionally graded structure were electrodeposited using a continuous variation of duty cycle/frequency within eight stages. Scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) were employed for microstructure and elemental analysis, respectively. The atomic force microscopy (AFM) and profilometry analyses were used to investigate the roughness of coatings. Results showed copper and alumina contents increased, while nickel and tungsten contents decreased toward the surface with a continuous drop in duty cycle. Continuous variation of pulse frequency showed a different manner, however; as it was found less effective than duty cycle. The observed contact angle demonstrated that the produced coatings have hydrophobic properties owing to their hierarchical morphology. In addition, the pin-on-disk wear test results indicated that the predominant controlling wear mechanism might be described as the abrasive wear created by the abrasive grooves. Graphical abstract: Highlights: Electrodeposition of Ni-Cu-W-Al2 O3 was carried out with gradient structure. Gradient structure was achieved by targeted adjusting pulse parameters. Cu & Al2 O3 increase and Ni & W decrease gradually as a function of coating thickness. High frequency deposited coatings demonstrate more resistance against wear. Hierarchical morphology brings the hydrophobicity of coatings.